(untitled) (Research, Society and Development, 2023)
Despite similarity to other cell types, the sperm has a compacted chromatin which makes DNA extraction more difficult. Based on this, this study compared different sperm concentrations and three DNA extraction techniques to use in qPCR. Four protocols were tested: a non-commercial using phenol:chloroform (M1) alone or associated with a preparatory kit (Differex-System-Kit-M2), and two commercial with mini-columns extraction: M3 (Illustra-Blood-Genomic-Prep-Mini-Spin) and M4 (Wizard®-Genomic-DNA-Purification). Four sperm concentrations were used (1, 10, 30 and 50x106) from ejaculates of 3 dogs. After extraction, the DNA was used for qPCR with primers directed against X and Y chromosomes. M1 and M2 protocols recovered high DNA concentration independently of initial sperm concentration, with a satisfactory ratio of 260/280 absorbances (mean 1.80 and 2.10, M1 and M2 respectively). In contrast, other methods recovered low DNA concentration and with poor quality in M3 (mean 1.60 in M3 and 1.85 in M4). The DNA extraction of canine sperm cells using protocols with phenol:chloroform (M1 and M2) was efficient. The M1 protocol notably allowed the quantification of X and Y chromosomes in qPCR using low number of sperm cells (1x106). This study provides the first comparison of DNA extraction techniques of canine sperm and it is concluded that independent of sperm concentration used, including use of only 1x106 sperm, DNA extraction from these cells using phenol:chloroform has satisfactory results regarding the quantity and quality of the extracted sample, and enabled quantitation of target gene sequences in qPCR, allowing subsequent use in sperm sexing and other biotechnologies.